Intracranial Hypotension and Hypertension Associated With Reconstructive Cranioplasty After Decompressive Craniectomy: Report of a Lethal Complication With Recommended Strategies for Future Avoidance. Issue 7 (October 2018) - Dalle Ore, Cecilia L.; Abraham, Peter; Burns, Luke P.; Lance, Samuel; Gosman, Amanda; Meltzer, Hal S.
Abstract : Abstract: Reconstructive cranioplasty can be associated with many complications and add to the not insignificant potential risks associated with decompressive craniectomy. In the setting of post-traumatic hydrocephalus, treatment with a ventriculoperitoneal (VP) shunt prior to reconstructive cranioplasty likely increases these risks even further. The authors report a case of a 17-year-old male with a history of a severe closed head injury who initially suffered a life-threatening complication associated with intracranial hypotension after cranioplasty only to succumb to malignant intracranial hypertension following a second cranioplasty attempt. To our knowledge, this is the first description of a single patient developing both these disparate complications after reconstructive cranioplasty and emphasizes the likely synergistic hazards involved with decompressive craniectomy in the setting of a VP shunt in particular and the overall myriad potential complications that may be associated with reconstructive cranioplasty in general.